Sex hormone-specific regulation of ferroptosis in vascular cells in atherosclerosis: molecular mechanisms and targeted strategies - Yu, Keying; Li, Jitong; Tian, Tenghui; Shi, Rui; Deng, Yue; Chang, Liping (Frontiers in Physiology, 2025)
Atherosclerosis (AS), the leading cause of cardiovascular morbidity and mortality worldwide, exhibits significant sex differences in its incidence and pathological progression, yet the underlying molecular mechanisms remain fully elucidated. Ferroptosis, a form of regulated cell death driven by iron-dependent lipid peroxidation, has recently been identified as a key pathological event contributing to the progression of AS. The basis of physiological sex dimorphism is composed of both circulating sex hormone levels and cell-intrinsic sex differences, which may play a critical role in determining the sex-specific characteristics of AS by modulating the ferroptosis signaling network. This review aims to systematically elaborate and substantiate the “sex hormone-ferroptosis regulatory axis” as a pivotal theoretical framework in the context of AS-related sex differences. We integrate existing evidence suggesting that estrogen can synergistically inhibit ferroptosis in vascular cells, particularly endothelial cells and macrophages, through multiple pathways. These include: (1) activating the central antioxidant system driven by Nuclear Factor Erythroid 2-Related Factor 2 (Nrf2); (2) regulating mitochondrial homeostasis and function; and (3) directly modulating key iron metabolism proteins, such as upregulating the iron efflux protein Ferroportin-1 (FPN1). These mechanisms collectively contribute to the cardiovascular protective effects observed in premenopausal women. Conversely, available evidence suggests that androgens may promote ferroptosis in vascular cells by enhancing oxidative stress, potentially increasing cellular iron uptake (e.g., through potential upregulation of Transferrin Receptor 1, TFR1), and modulating lipid metabolism to increase the availability of peroxidizable substrates. This could be a significant contributor to the earlier onset and higher incidence of AS in men. Based on this framework, this review further explores potential sex-specific therapeutic strategies targeting this regulatory axis. This review provides a novel molecular perspective for understanding the sex differences in AS and provides a theoretical basis for the development of a new paradigm in sex-stratified precision cardiovascular medicine.